Outcomes and mechanical complications of acute myocardial infarction during the second wave pandemic in a Milan HUB center for cardiac emergencies - Penso, Marco; Frappampina, Antonio; Cosentino, Nicola; Tamborini, Gloria; Celeste, Fabrizio; Ianniruberto, Monica; Ravagnani, Paolo; Troiano, Sarah; Marenzi, Giancarlo; Pepi, Mauro (Frontiers in Cardiovascular Medicine, 2022)
Aims: The COVID-19 has dramatically impacted the healthcare system. Previous evidence suggests a decline in-hospital admission for acute myocardial infarction (AMI) during pandemic. However, the effect of pandemic on mechanical complications (MC) in acute ST-segment elevation myocardial infarction (STEMI) has not been comprehensively investigated. We evaluated the impact of the pandemic on MC and in-hospital outcomes in STEMI, during the second wave, in which there was a huge SARS-CoV-2 diffusion in Italy. Methods and results: Based on a single center cohort of AMI patient admitted with STEMI between 1 February 2019 and 28 February 2021, we compared characteristics and outcomes of STEMI patients treated during pandemic versus those treated before pandemic. In total, 479 STEMI patients were included, of which 64.5% during the pandemic. Relative to before pandemic, primary percutaneous coronary intervention (PCI) declined (87.7% vs. 94.7%, p=0.014) during pandemic. As compared to those before the pandemic (10/2019 to 2/2020), STEMI patients admitted during the second wave (10/2020 to 2/2021) presented more frequency symptoms’ onset-to-door time longer than 24 hours (26.1% vs. 10.3%, p=0.009) and a reduction of primary PCI (85.2% vs. 97.1%, p=0.009). MC occurred more often in patients admitted during the second wave of pandemic, as compared to those admitted before the pandemic (7.0% vs. 0.0%, p=0.032). In-hospital mortality increased during the second wave (10.6% vs. 2.9%, p=0.058). Conclusions: Although the experience gained during the first wave and a more advanced hub-and-spoke system for cardiovascular emergencies, even in the second wave persists late hospitalizations and high incidence of mechanical complication in STEMI.